Acquisition of behavioral avoidance: Task-irrelevant conditioned stimuli trigger costly decisions - Pittig, Andre; Schulz, Alexandra R.; Craske, Michelle G.; Alpers, Georg W. (Journal of Abnormal Psychology, 2014)
Individuals avoid stimuli which are associated with aversive experience to preserve safety. However, behavioral avoidance also causes impairments and prevents the individual from attaining positive rewards. Little is known about the link between fear acquisition and the development of behavioral avoidance in the presence of potential rewards. Therefore, two experiments investigated the impact of fear conditioning on a subsequent gambling task. In an experimental group (n = 30) advantageous choices (higher reward probability) were linked to a fear-relevant stimulus that was associated with an aversive unconditioned stimulus (US) during fear conditioning (conditioned stimulus, CS+). A disadvantageous choice (lower reward probability) was, however, linked to a safe stimulus that was never associated with the US (CS-). In a control group (n = 25), fear conditioning was followed by a similar gambling task with novel stimuli. A second experiment focused on individual predictors of avoidant decisions (n = 81). Compared with the control group, individuals in the experimental groups avoided the advantageous CS + choice despite fewer gains. The predictor analysis further clarified that avoidant decisions were pronounced in highly trait anxious participants who exhibited higher fear responses. On the other hand, findings also indicated a reduction in absolute avoidance across the task. Combined, these findings demonstrate that fear conditioning can lead to avoidant decision making, especially in vulnerable individuals. The resulting costs parallel impairments caused by behavioral avoidance. Such an emotional decision-making style may be a link between aversive experience and the development of habitual pathological avoidance. Introducing rewards for approach, however, may counteract avoidant decisions. © 2014 American Psychological Association.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety; Approach-avoidance conflict; Behavioral avoidance; Decision making; Experimental psychopathology; Fear conditioning

A dimensional measure of safety behavior: A non-dichotomous assessment of costly avoidance in human fear conditioning - Wong, Alex H. K.; Pittig, Andre (Psychological research, 2021)
Safety behavior prevents the occurrence of threat, thus it is typically considered adaptive. However, safety behavior in anxiety-related disorders is often costly, and persists even the situation does not entail realistic threat. Individuals can engage in safety behavior to varying extents, however, these behaviors are typically measured dichotomously (i.e., to execute or not). To better understand the nuances of safety behavior, this study developed a dimensional measure of safety behavior that had a negative linear relationship with the admission of an aversive outcome. In two experiments, a Reward group receiving fixed or individually calibrated incentives competing with safety behavior showed reduced safety behavior than a Control group receiving no incentives. This allowed extinction learning to a previously learnt warning signal in the Reward group (i.e., updating the belief that this stimulus no longer signals threat). Despite the Reward group exhibited extinction learning, both groups showed a similar increase in fear to the warning signal once safety behavior was no longer available. This null group difference was due to some participants in the Reward group not incentivized enough to disengage from safety behavior. Dimensional assessment revealed a dissociation between low fear but substantial safety behavior to a safety signal in the Control group. This suggests that low-cost safety behavior does not accurately reflect the fear-driven processes, but also other non-fear-driven processes, such as cost (i.e., engage in safety behavior merely because it bears little to no cost). Pinpointing both processes is important for furthering the understanding of safety behavior.
CRIS-Team Scopus Importer:2021-05-26

A Systematic Review of Land-Based Self-Exclusion Programs: Demographics, Gambling Behavior, Gambling Problems, Mental Symptoms, and Mental Health - Kotter, Roxana; Kraeplin, Anja; Pittig, Andre; Buehringer, Gerhard (Journal of Gambling Studies, 2019)
Systematic and quantitative reviews on the effects of land-based self-exclusion are scarce. Therefore, the current review aimed to provide a comprehensive summary of (1) the demographic characteristics of land-based self-excluders and changes after exclusion, including (2) gambling behavior, (3) gambling problems, (4) mental symptoms, and (5) mental health. A systematic database and literature search was performed following PRISMA guidelines. Nineteen naturalistic studies met the eligibility criteria. The quality of all included records was rated via adaption of the Newcastle-Ottawa Scale. Results from higher-quality records were more heavily weighted. Self-excluders were predominantly men in their early or middle forties. Changes after exclusion revealed wide ranges in the rates of abstinence (13-81%), rates of gambling reduction (29-92%), and rates of exclusion breaches (8-59%). The records consistently demonstrated significant changes in pathological gambling from before exclusion (61-95%) to after exclusion (13-26%). Up to 73% of self-excluders exhibited symptoms of anxiety, depression, and substance use disorders at program enrollment. Several aspects of mental health improved after exclusion, e.g., quality of life. Problem and pathological gambling are most prevalent in young men, but self-exclusion was most prominent in middle-aged men. The magnitude of effects widely differed between studies despite overall benefits of self-exclusion, and many individuals continued gambling after exclusion. This shortcoming could be minimized using improved access controls and the extension of exclusion to other gambling segments. High rates of pathological gambling and other mental disorders in self-excluders highlight the need for improved early detection and treatment accessibility.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Casino; Comorbidity; Evaluation; Gambling; Prevention; Self-exclusion

Avoidance and its bi-directional relationship with conditioned fear: Mechanisms, moderators, and clinical implications - Pittig, Andre; Wong, Alex H. K.; Glueck, Valentina M.; Boschet, Juliane M. (Behaviour Research and Therapy, 2020)
Fear motivates different types of defensive behaviors. These behaviors are, however, not mere byproducts of fear. In this review, we highlight a bi-directional relationship between conditioned fear and instrumental defensive behavior in humans. We discuss mechanisms involved in the link from fear to goal-directed avoidance (e.g., relief, generalization), that may become habitual. These defensive behaviors may in turn reduce, preserve, or amplify fear responding (e.g., protection-from-extinction, behavior-as-information). Multiple factors moderate the bi-directional relationship. Evidence for amplifying and dampening effects of inter-individual differences (e.g., trait anxiety, distress tolerance), intra-individual states (e.g., stress), and external factors (e.g., incentives for competing behavior) on goal-directed and/or habitual defensive behavior is reviewed. However, the exact mechanisms by which these factors moderate the bi-directional relationship are still largely unknown (e.g., modulating avoidance directly vs. indirectly via conditioned fear). Finally, we discuss major implications: First, understanding factors moderating the bi-directional relationship provides insights into risk and resilience factors for anxious psychopathology. Second, specific experimental models and clinical interventions can be mapped onto distinct defensive behaviors (e.g., goal-directed vs. habitual avoidance). More precise matching will help to develop nuanced models and interventions to reduce pathological behaviors and individualize treatments.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety; Aversive conditioning; Avoidance; Defensive behavior; Fear conditioning; Habits; Instrumental behavior; Safety behavior

Avoidance of learnt fear: Models, potential mechanisms, and future directions - Wong, Alex H.K.; Wirth, Franziska M.; Pittig, Andre (Behaviour Research and Therapy, 2022)
Avoiding stimuli that were previously associated with threat is essential for adaptive functioning, but excessive avoidance that persists in the absence of threat can turn dysfunctional and results in severe impairments. Fear and avoidance conditioning models have substantially contributed to the understanding of safety behaviors towards learnt fear stimuli. Safety behaviors are executed in the presence of a feared stimulus to prevent the upcoming threat and are well-established in laboratory models. Avoidance of learnt fear, i.e., avoidance of the feared stimulus itself, is typically initiated before the onset of a feared stimulus: individuals oftentimes avoid fear stimuli to prevent negative emotions evoked by them or ultimately the associated threat. Avoidance of learnt fear is surprisingly understudied despite its prevalence in pathological anxiety. The current overview proposes potential behavioral mechanisms and neural circuits of avoidance of learnt fear in humans, and discusses findings and paradigms suitable for examining it. Specifically, higher-order conditioning, decision making paradigms, and context-cue conditioning investigate distinct forms of avoidance of learnt fear. We also discuss the clinical prospects and future directions of research in avoidance of learnt fear.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Anxiety-related disorders; Associative learning; Avoidance; CS-Avoidance; Extinction; Fear conditioning

Avoidant decision-making in social anxiety disorder: A laboratory task linked to in vivo anxiety and treatment outcome - Pittig, Andre; Alpers, Georg W.; Niles, Andrea N.; Craske, Michelle G. (Behaviour Research and Therapy, 2015)
Recent studies on reward-based decision-making in the presence of anxiety-related stimuli demonstrated that approach-avoidance conflicts can be assessed under controlled laboratory conditions. However, the clinical relevance of these decision conflicts has not been demonstrated. To this end, the present study investigated avoidant decisions in treatment-seeking individuals with social anxiety disorder (SAD). In a gambling task, advantageous choices to maximize gains were associated with task-irrelevant angry faces and disadvantageous choices with happy faces. The clinical relevance of avoidant decisions for in vivo anxiety in a social stress situation (public speaking) were examined (n = 44). In a subsample (n = 20), the predictive value for a reduction of avoidance following behavioral therapy was also evaluated. Results indicated a close link between more frequent avoidant decisions and elevated in vivo anxiety. Moreover, individuals who showed a deficit in the goal-directed adjustment of their decisions also showed higher and sustained distress during the social stressor and reported less decrease of avoidance following treatment. The findings highlight the importance of an avoidant decision-making style for the experience of acute distress and the maintenance of avoidance in SAD. Assessing avoidant decision-making may help to predict the response to behavioral treatments.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Avoidance; Decision making; Experimental psychopathology; Facial expressions; Goal-directed behavior; Incentives; Social anxiety disorder

Avoidant decision making in social anxiety: The interaction of angry faces and emotional responses - Pittig, Andre; Pawlikowski, Mirko; Craske, Michelle G.; Alpers, Georg W. (Frontiers in Psychology, 2014)
Recent research indicates that angry facial expressions are preferentially processed and may facilitate automatic avoidance response, especially in socially anxious individuals. However, few studies have examined whether this bias also expresses itself in more complex cognitive processes and behavior such as decision making. We recently introduced a variation of the Iowa Gambling Task which allowed us to document the influence of task-irrelevant emotional cues on rational decision making. The present study used a modified gambling task to investigate the impact of angry facial expressions on decision making in 38 individuals with a wide range of social anxiety. Participants were to find out which choices were (dis-) advantageous to maximize overall gain. To create a decision conflict between approach of rewards and avoidance of fear-relevant angry faces, advantageous choices were associated with angry facial expressions, whereas disadvantageous choices were associated with happy facial expressions. Results indicated that higher social avoidance predicted less advantageous decisions in the beginning of the task, i.e., when contingencies were still uncertain. Interactions with specific skin conductance responses further clarified that this initial avoidance only occurred in combination with elevated responses before choosing an angry facial expressions. In addition, an interaction between high trait anxiety and elevated responses to early losses predicted faster learning of an advantageous strategy. These effects were independent of intelligence, general risky decision-making, self-reported state anxiety, and depression. Thus, socially avoidant individuals who respond emotionally to angry facial expressions are more likely to show avoidance of these faces under uncertainty. This novel laboratory paradigm may be an appropriate analog for central features of social anxiety.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Behavioral avoidance; Decision making; Facial expressions; Psychopathology; Social anxiety

Avoiding a feared stimulus: Modelling costly avoidance of learnt fear in a sensory preconditioning paradigm - Wong, Alex H.K.; Pittig, Andre (Biological Psychology, 2022)
Avoidance of learnt fear prevents the onset of a feared stimulus and the threat that follows. In anxiety-related disorders, it turns pathological given its cost and persistence in the absence of realistic threat. The current study examined the acquisition of costly avoidance of learnt fear in healthy individuals (n = 45), via a sensory preconditioning paradigm. Two neutral preconditioning stimuli (PSs) were paired with two neutral conditioned stimuli (CSs). One CS then came to predict an aversive outcome whereas the other CS came to predict safety. In test, participants engaged in stronger avoidance to the PS associated with the fear-related CS than the PS associated with the safety-related CS. Of note, executing behavioral avoidance led to missing out a competing reward, thus rendering avoidance costly. The results also provide preliminary evidence that threat anticipation and a negative change in valence play a role in driving costly avoidance of learnt fear. Future studies should examine how avoidance of learnt fear maintains pathological anxiety.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Anxiety; Avoidance; Costly avoidance; Fear conditioning; Higher-order conditioning; Threat anticipation

Barrieren und Strategien bei der Anwendung expositionsbasierter Verfahren in der niedergelassenen Praxis. - Rumin, Elena; Pittig, Andre; Hoyer, Juergen (Verhaltenstherapie und psychosoziale Praxis, 2019)

Bridging the gaps between basic science and cognitive-behavioral treatments for anxiety disorders in routine care: Current status and future demands - Richter, Jan; Pittig, Andre; Hollandt, Maike; Lueken, Ulrike (Journal of Psychology / Zeitschrift für Psychologie, 2017)
As a core component of cognitive-behavioral therapies (CBT), behavioral exposure is an effective treatment for anxiety disorders. Still, recent treatment studies demonstrate relatively high rates of treatment dropout, nonresponse, and relapse, indicating a substantial need for optimizing and personalizing existing treatment procedures. In the present article, we aim to address current challenges and future demands for translational research in CBT for the anxiety disorders, including (a) a better understanding of those mechanisms conferring behavioral change, (b) identifying important sources of individual variation that may act as moderators of treatment response, and (c) targeting practical barriers for dissemination of exposure therapy to routine care. Based on a recursive process model of psychotherapy research we will describe distinct steps to systematically translate basic and clinical research "from bench to bedside" to routine care, but also vice versa. Some of these aspects may stimulate the future roadmap for evidence-based psychotherapy research in order to better target the treatment of anxiety disorders as one core health challenge of our time.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Cognitive-behavioral therapy (CBT); Exposure; Individualized psychotherpy; Routine care

Change of Threat Expectancy as Mechanism of Exposure-Based Psychotherapy for Anxiety Disorders: Evidence From 8,484 Exposure Exercises of 605 Patients - Pittig, Andre; Heinig, Ingmar; Goerigk, Stephan; Richter, Jan; Hollandt, Maike; Lueken, Ulrike; Pauli, Paul; Deckert, Jurgen; Kircher, Tilo; Straube, Benjamin; Neudeck, Peter; Koelkebeck, Katja; et al. (Clinical Psychological Science, 2022)
Individual responses to behavioral treatment of anxiety disorders vary considerably, which requires a better understanding of underlying processes. In this study, we examined the violation and change of threat beliefs during exposure. From 8,484 standardized exposure records of 605 patients with different anxiety disorders, learning indicators were derived: expectancy violation as mismatch between threat expectancy before exposure and threat occurrence, expectancy change as difference between original and adjusted expectancy after exposure, and prediction-error learning rate as extent to which expectancy violation transferred into change. Throughout sessions, high threat expectancy but low occurrence and adjusted expectancy indicated successful violation and change of threat beliefs by exposure. Expectancy violation, change, and learning rate substantially varied between patients. Not expectancy violation itself, but higher learning rate and expectancy change predicted better treatment outcome. Successful exposure thus requires expectancy violation to induce actual expectancy change, supporting learning from prediction error as transdiagnostic mechanism underlying successful exposure therapy.
CRIS-Team WoS Importer:2022-10-21

Costly avoidance in anxious individuals: Elevated threat avoidance in anxious individuals under high, but not low competing rewards - Pittig, Andre; Scherbaum, Stefan (Journal of Behavior Therapy and Experimental Psychiatry, 2020)
Background and objectives: When avoiding threat conflicts with approaching rewards, balanced responses to threat and reward information is required to guide functional behavior. Elevated threat avoidance characterizes anxious psychopathology. However, little is known about the mutual impact of threat and reward information on approach-avoidance behavior and its link to anxiety. Methods: High trait-anxious and low-anxious individuals (N = 74) repeatedly choose between two options. A threat/high-reward option was linked to two outcomes: a varying chance to receive an aversive stimulus and a varying high reward. A safe/low-reward option was linked to absence of the aversive stimulus and a low reward. Results: Avoidance of the threat/high-reward option increased with increasing threat. Despite threat, low-anxious individuals increasingly approached the threat/high-reward option when rewards increased. High- compared to low-anxious individuals showed elevated avoidance, but only in the presence of high competing rewards. Limitations: Future research should examine boundary conditions by manipulating type and motivational value of appetitive and aversive outcomes (e.g., food as primary reinforcer). Conclusions: These findings suggest that a weaker impact of rewards competing with threat contributes to elevated threat avoidance in anxious psychopathology. Costly avoidance may thus be a factor involved in anxious psychopathology.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety; Approach-avoidance behavior; Avoidance; Discounting

Costly avoidance of Pavlovian fear stimuli and the temporal dynamics of its decision process - Boschet, Juliane M.; Scherbaum, Stefan; Pittig, Andre (Scientific Reports, 2022)
Conflicts between avoiding feared stimuli versus approaching them for competing rewards are essential for functional behavior and anxious psychopathology. Yet, little is known about the underlying decision process. We examined approach-avoidance decisions and their temporal dynamics when avoiding Pavlovian fear stimuli conflicted with gaining rewards. First, a formerly neutral stimulus (CS+) was repeatedly paired with an aversive stimulus (US) to establish Pavlovian fear. Another stimulus (CS−) was never paired with the US. A control group received neutral tones instead of aversive USs. Next, in each of 324 trials, participants chose between a CS−/low reward and a CS+/high reward option. For the latter, probability of CS+ presentation (Pavlovian fear information) and reward magnitude (reward information) varied. Computer mouse movements were tracked to capture the decision dynamics. Although no more USs occurred, pronounced and persistent costly avoidance of the Pavlovian fear CS+ was found. Time-continuous multiple regression of movement trajectories revealed a stronger and faster impact of Pavlovian fear compared to reward information during decision-making. The impact of fear information, but not reward information, modestly decreased across trials. These findings suggest a persistently stronger weighting of fear compared to reward information during approach-avoidance decisions, which may facilitate the development of pathological avoidance.
CRIS-Team Scopus Importer:2022-05-06

Costly avoidance triggered by categorical fear generalization - Wong, Alex H. K.; Pittig, Andre (Behaviour Research and Therapy, 2020)
Fear generalization refers to the spread of acquired fear to novel stimuli that resemble the original fear-related stimulus. Preliminary evidence suggests that excessive fear generalization is a pathogenic feature of anxiety disorders, however, it remains unclear how fear generalization affects pathological avoidance. The current study thus aimed to examine the link between categorical fear generalization and costly avoidance. By combining a fear acquisition training phase and an avoidance test, the current findings showed that acquired fear spreads to novel stimuli that belonged to the same category of the original fear-related stimuli, but not to those that belonged to the fear-irrelevant categories. Importantly, participants avoided these fear-related novel stimuli despite costs. The current findings indicate that categorical fear generalization triggers costly avoidance. In terms of clinical implication, a decrease in costly avoidance aligned with a decrease in US expectancies. This emphasizes that behavioral approach may initiate extinction learning.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Approach-avoidance conflict; Avoidance; Categorical generalization; Cost; Fear conditioning; Fear generalization

Costly habitual avoidance is reduced by concurrent goal-directed approach in a modified devaluation paradigm - Glück, Valentina M.; Zwosta, Katharina; Wolfensteller, Uta; Ruge, Hannes; Pittig, Andre (Behaviour Research and Therapy, 2021)
Avoidance habits potentially contribute to maintaining maladaptive, costly avoidance behaviors that persist in the absence of threat. However, experimental evidence about costly habitual avoidance is scarce. In two experiments, we tested whether extensively trained avoidance impairs the subsequent goal-directed approach of rewards. Healthy participants were extensively trained to avoid an aversive outcome by performing simple responses to distinct full-screen color stimuli. After the subsequent devaluation of the aversive outcome, participants received monetary rewards for correct responses to neutral object pictures, which were presented on top of the same full-screen colors. These approach responses were either compatible or incompatible with habitual avoidance responses. Notably, the full-screen colors were not relevant to inform approach responses. In Experiment 1, participants were not instructed about post-devaluation stimulus-response-reward contingencies. Accuracy was lower in habit-incompatible than in habit-compatible trials, indicating costly avoidance, whereas reaction times did not differ. In Experiment 2, contingencies were explicitly instructed. Accuracy differences disappeared, but reaction times were slower in habit-incompatible than in habit-compatible trials, indicating low-cost habitual avoidance tendencies. These findings suggest a small but consistent impact of habitual avoidance tendencies on subsequent goal-directed approach. Costly habitual responding could, however, be inhibited when competing goal-directed approach was easily realizable.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Costly avoidance; Devaluation paradigm; Goal-directed behavior; Habit

Diagnostik bei Generalisierten Angststörung - Hoyer, Juergen; Pittig, Andre (Diagnostik in der Psychotherapie - Ein Praxisleitfaden, 2017)

Do Changes in Dysfunctional Posttraumatic Cognitions Differentially Predict PTSD Symptom Clusters? - Schumm, Hannah; Krueger-Gottschalk, Antje; Ehring, Thomas; Dyer, Anne; Pittig, Andre; Takano, Keisuke; Alpers, Georg W. W.; Cludius, Barbara (Journal of Consulting and Clinical Psychology, 2023)
Objective: In recent years, it has been suggested that the modification of dysfunctional posttraumatic cognitions plays a central role as a mechanism of change in cognitive behavioral therapy (CBT) for posttraumatic stress disorder (PTSD). Indeed, several studies have shown that changes in dysfunctional posttraumatic cognitions precede and predict symptom change. However, these studies have investigated the influence on overall symptom severity-despite the well-known multidimensionality of PTSD. The present study therefore aimed to explore differential associations between change in dysfunctional conditions and change in PTSD symptom clusters. Method: As part of a naturalistic effectiveness study evaluating trauma-focused cognitive behavioral therapy for PTSD in routine clinical care, 61 patients with PTSD filled out measures of dysfunctional posttraumatic cognitions and PTSD symptom severity every five sessions during the course of treatment. Lagged associations between dysfunctional cognitions and symptom severity at the following timepoint were examined using linear mixed models. Results: Over the course of therapy, both dysfunctional cognitions and PTSD symptoms decreased. Posttraumatic cognitions predicted subsequent total PTSD symptom severity, although this effect was at least partly explained by the time factor. Moreover, dysfunctional cognitions predicted three out of four symptom clusters as expected. However, these effects were no longer statistically significant when the general effect for time was controlled for. Conclusion: The present study provides preliminary evidence that dysfunctional posttraumatic cognitions predict PTSD symptom clusters differentially. However, different findings when employing a traditional versus a more rigorous statistical approach make interpretation of findings difficult.
CRIS-Team WoS Importer:2023-05-26

Don't fear ‘fear conditioning’: Methodological considerations for the design and analysis of studies on human fear acquisition, extinction, and return of fear - Lonsdorf, Tina B.; Menz, Mareike M.; Andreatta, Marta; Fullana, Miguel A.; Golkar, Armita; Haaker, Jan; Heitland, Ivo; Hermann, Andrea; Kuhn, Manuel; Kruse, Onno; Drexler, Shira Meir; Meulders, Ann; et al. (Neuroscience and Biobehavioral Reviews, 2017)
The so-called ‘replicability crisis’ has sparked methodological discussions in many areas of science in general, and in psychology in particular. This has led to recent endeavours to promote the transparency, rigour, and ultimately, replicability of research. Originating from this zeitgeist, the challenge to discuss critical issues on terminology, design, methods, and analysis considerations in fear conditioning research is taken up by this work, which involved representatives from fourteen of the major human fear conditioning laboratories in Europe. This compendium is intended to provide a basis for the development of a common procedural and terminology framework for the field of human fear conditioning. Whenever possible, we give general recommendations. When this is not feasible, we provide evidence-based guidance for methodological decisions on study design, outcome measures, and analyses. Importantly, this work is also intended to raise awareness and initiate discussions on crucial questions with respect to data collection, processing, statistical analyses, the impact of subtle procedural changes, and data reporting specifically tailored to the research on fear conditioning.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Conditioning; Design; Extinction; Individual differences; Methods; Methods; Replicability crisis; Return of fear; Statistics; Terminology

Effective—and Tolerable: Acceptance and Side Effects of Intensified Exposure for Anxiety Disorders - Heinig, Ingmar; Knappe, Susanne; Hoyer, Jürgen; Wittchen, Hans Ulrich; Richter, Jan; Arolt, Volker; Deckert, Jürgen; Domschke, Katharina; Hamm, Alfons; Kircher, Tilo; Lueken, Ulrike; Margraf, Jürgen; et al. (Behavior Therapy, 2023)
Despite striking empirical support, exposure-based treatments for anxiety disorders are underutilized. This is partially due to clinicians’ concerns that patients may reject exposure or experience severe side effects, particularly in intensive forms of exposure. We examined acceptance and side effects of two randomly assigned variants of prediction error-based exposure treatment differing in temporal density (1 vs. 3 sessions/week) in 681 patients with panic disorder, agoraphobia, social anxiety disorder, and multiple specific phobias. Treatment acceptance included treatment satisfaction and credibility, engagement (i.e., homework completion), and tolerability (i.e., side effects, dropout, and perceived treatment burden). Side effects were measured with the Inventory for the Balanced Assessment of Negative Effects of Psychotherapy (INEP). We found treatment satisfaction, credibility, and engagement to be equally high in both variants of exposure-based treatment, despite higher treatment burden (β = 0.25) and stronger side effects (β = 0.15) in intensified treatment. 94.1% of patients reported positive effects in the INEP. 42.2% reported side effects, with treatment stigma (16.6%), low mood (14.8%) and the experience to depend on the therapist (10.9%) being the most frequently reported. The mean intensity of side effects was low. We conclude that prediction error-based exposure treatment is well accepted by patients with different anxiety disorders and that patients also tolerate temporally intensified treatment, despite higher perceived treatment burden and stronger side effects. Clinicians should be aware of the most frequent side effects to take appropriate countermeasures. In sum, temporal intensification appears to be an acceptable strategy to achieve faster symptom reduction, given patients’ well-informed consent.
CRIS-Team Scopus Importer:2023-02-17
Keywords: anxiety disorders; intensified exposure; negative effects of psychotherapy; side effects; treatment acceptability

Efficacy of temporally intensified exposure for anxiety disorders: A multicenter randomized clinical trial - Pittig, Andre; Heinig, Ingmar; Goerigk, Stephan; Thiel, Freya; Hummel, Katrin; Scholl, Lucie; Deckert, Jurgen; Pauli, Paul; Domschke, Katharina; Lueken, Ulrike; Fydrich, Thomas; Fehm, Lydia; et al. (Depression and Anxiety, 2021)
Background: The need to optimize exposure treatments for anxiety disorders may be addressed by temporally intensified exposure sessions. Effects on symptom reduction and public health benefits should be examined across different anxiety disorders with comorbid conditions. Methods: This multicenter randomized controlled trial compared two variants of prediction error-based exposure therapy (PeEx) in various anxiety disorders (both 12 sessions + 2 booster sessions, 100 min/session): temporally intensified exposure (PeEx-I) with exposure sessions condensed to 2 weeks (n = 358) and standard nonintensified exposure (PeEx-S) with weekly exposure sessions (n = 368). Primary outcomes were anxiety symptoms (pre, post, and 6-months follow-up). Secondary outcomes were global severity (across sessions), quality of life, disability days, and comorbid depression. Results: Both treatments resulted in substantial improvements at post (PeEx-I: dwithin = 1.50, PeEx-S: dwithin = 1.78) and follow-up (PeEx-I: dwithin = 2.34; PeEx-S: dwithin = 2.03). Both groups showed formally equivalent symptom reduction at post and follow-up. However, time until response during treatment was 32% shorter in PeEx-I (median = 68 days) than PeEx-S (108 days; TRPeEx-I = 0.68). Interestingly, drop-out rates were lower during intensified exposure. PeEx-I was also superior in reducing disability days and improving quality of life at follow-up without increasing relapse. Conclusions: Both treatment variants focusing on the transdiagnostic exposure-based violation of threat beliefs were effective in reducing symptom severity and disability in severe anxiety disorders. Temporally intensified exposure resulted in faster treatment response with substantial public health benefits and lower drop-out during the exposure phase, without higher relapse. Clinicians can expect better or at least comparable outcomes when delivering exposure in a temporally intensified manner.
Created from Fastlane, Scopus look-up
Keywords: anxiety disorders; exposure therapy; intensified treatment; public health; randomized controlled trial

Elevated costly avoidance in anxiety disorders: Patients show little downregulation of acquired avoidance in face of competing rewards for approach - Pittig, Andre; Boschet, Juliane M.; Gluck, Valentina M.; Schneider, Kristina (Depression and Anxiety, 2021)
Background: Pathological avoidance is a transdiagnostic characteristic of anxiety disorders. Avoidance conditioning re-emerged as a translational model to examine mechanisms and treatment of avoidance. However, its validity for anxiety disorders remains unclear. Methods: This study tested for altered avoidance in patients with anxiety disorders compared to matched controls (n = 40/group) using instrumental conditioning assessing low-cost avoidance (avoiding a single aversive outcome) and costly avoidance (avoidance conflicted with gaining rewards). Autonomic arousal and threat expectancy were assessed as indicators of conditioned fear. Associations with dimensional symptom severity were examined. Results: Patients and controls showed frequent low-cost avoidance without group differences. Controls subsequently inhibited avoidance to gain rewards, which was amplified when aversive outcomes discontinued. In contrast, patients failed to reduce avoidance when aversive and positive outcomes competed (elevated costly avoidance) and showed limited reduction when aversive outcomes discontinued (persistent costly avoidance). Interestingly, elevated costly avoidance was not linked to higher conditioned fear in patients. Moreover, individual data revealed a bimodal distribution of costly avoidance: Some patients showed persistent avoidance, others showed little to no avoidance. Persistent versus low avoiders did not differ in other task-related variables, response to gains and losses in absence of threat, sociodemographic data, or clinical characteristics. Conclusions: Findings suggest that anxious psychopathology is associated with a deficit to inhibit avoidance in presence of competing positive outcomes. This offers novel perspectives for research on mechanisms and treatment of anxiety disorders.
CRIS-Team Scopus Importer:2021-05-26
Keywords: anxiety disorders; approach-avoidance conflict; fear conditioning; instrumental avoidance; panic disorder and agoraphobia; social anxiety disorder

Exposition aus Sicht niedergelassener Verhaltenstherapeutinnen und Verhaltenstherapeuten: Anwendung und systemische Barrieren [Utilization and barriers of exposure in private practice: The perspective of behavioral psychotherapists ] - Pittig, Andre; Hoyer, Juergen (Zeitschrift für Klinische Psychologie und Psychotherapie, 2017)
Background: Exposure-based interventions are one of the most effective techniques for the treatment of anxiety disorders. Previous research, however, indicated that exposure is rarely utilized in routine care. Barriers that prevent the utilization of exposure in routine care have not been systematically examined. Method: The present study aimed to assess barriers of exposure utilization related to the German health-care system as well as favored changes from the perspective of behavioral therapists working in routine care. Barriers and self-reported frequency of exposure utilization were assessed via postal survey (N = 684). Results: Self-reported utilization indicated that some form of exposure was utilized in less than half of the treatments focusing on an anxiety disorder (46.8 %), which varied strongly between therapists. If utilized, exposure was mainly conducted in the clinician's office, for an average of 1 hr per exposure exercise, and at a weekly or biweekly frequency. More frequent utilization was associated with younger age, a lower number of years working as a therapist, and a higher number of exposure-related hours during clinical training and qualification. Frequent barriers were especially related to financial factors and the effort-compensation ratio, uncertainties about legal liability when conducting exposure outside one's office, and a limited amount of insurance-granted sessions. Conclusion: Exposure for anxiety disorders still seems to be less frequently and intensively utilized as suggested by current evidenced-based practice guidelines. A variety of barriers within the health-care system hamper the utilization by behavioral therapists working in routine care.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Dissemination; Exposure therapy; Routine care

Exposition - Pittig, Andre; Neudeck, Peter (Zeitschrift für Klinische Psychologie und Psychotherapie, 2017)

Expositions- und Konfrontationsverfahren - Lang, Thomas; Pittig, Andre; Jacobi, Frank (Verhaltenstherapie in der Praxis, 2017)

Face-to-face: Perceived personal relevance amplifies face processing - Bublatzky, Florian; Pittig, Andre; Schupp, Harald T.; Alpers, Georg W. (Social cognitive and affective neuroscience, 2017)
The human face conveys emotional and social information, but it is not well understood how these two aspects influence face perception. In order to model a group situation, two faces displaying happy, neutral or angry expressions were presented. Importantly, faces were either facing the observer, or they were presented in profile view directed towards, or looking away from each other. In Experiment 1 (n = 64), face pairs were rated regarding perceived relevance, wish-to-interact, and displayed interactivity, as well as valence and arousal. All variables revealed main effects of facial expression (emotional > neutral), face orientation (facing observer > towards > away) and interactions showed that evaluation of emotional faces strongly varies with their orientation. Experiment 2 (n = 33) examined the temporal dynamics of perceptual- attentional processing of these face constellations with event-related potentials. Processing of emotional and neutral faces differed significantly in N170 amplitudes, early posterior negativity (EPN), and sustained positive potentials. Importantly, selective emotional face processing varied as a function of face orientation, indicating early emotion-specific (N170, EPN) and late threat-specific effects (LPP, sustained positivity). Taken together, perceived personal relevance to the observer- conveyed by facial expression and face direction-amplifies emotional face processing within triadic group situations.
CRIS-Team Scopus Importer:2021-05-26
Keywords: EEG/ERP; Emotion; Face orientation; Facial expression; Personal relevance; Social interaction

From avoidance to approach: The influence of threat-of-shock on reward-based decision making - Bublatzky, Florian; Alpers, Georg W.; Pittig, Andre (Behaviour Research and Therapy, 2017)
Potential threat can prime defensive responding and avoidance behavior, which may result in the loss of rewards. When aversive consequences do not occur, avoidance should, thus, be quickly overcome in healthy individuals. This study examined the impact of threat anticipation on reward-based decisions. Sixty-five participants completed a decision-making task in which they had to choose between high- and low-reward options. To model an approach-avoidance conflict, the high-reward option was contingent with a threat-of-shock cue; the low-reward option was contingent with a safety cue. In control trials, decisions were made without threat/safety instructions. Overall, behavioral data documented a typical preference for the profitable option. Importantly, under threat-of-shock, participants initially avoided the profitable option (i.e., safe, but less profitable choices). However, when they experienced that shocks did actually not occur, participants overcame initial avoidance in favor of larger gains. Furthermore, autonomic arousal (skin conductance and heart rate responses) was elevated during threat cues compared to safety and non-threatening control cues. Taken together, threat-of-shock was associated with behavioral consequences: initially, participants avoided threat-related options but made more profitable decisions as they experienced no aversive consequences. Although socially acquired threat contingencies are typically stable, incentives for approach can help to overcome threat-related avoidance.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Behavioral avoidance; Decision making; Fear learning; Heart rate responses; Skin conductance responses; Threat-of-shock

Gambling problems seldom come alone: prevalence and temporal relationships of mental health problems in casino excluders - Kotter, R.; Kraeplin, A.; Pittig, Andre; Buehringer, G. (International Gambling Studies, 2019)
To estimate the effectiveness of gambling exclusion programmes, previous research focused on changes in gambling behaviour post-exclusion. Although other mental health problems, especially co-morbid mental disorders, may be crucial for relapse and recovery of gambling-related problems, these factors have rarely been studied in excluders. Therefore, this study aimed to assess a comprehensive mental health status of excluders using well-validated diagnostic instruments. Fifty-eight casino excluders participated in face-to-face diagnostic interviews and completed several validated questionnaires (e.g. Stinchfield Questionnaire, Brief Symptom Inventory). Retrospective temporal sequences of diagnosed mental disorders, help-seeking behaviour and exclusion were examined. The majority of excluders reported impairments in mental health aspects. About three-quarters met criteria of lifetime gambling disorder, more than half in the last 12 months whereby screening and diagnostic measures correlated moderately. Other mental disorders were frequent, especially affective and substance-related disorders and typically preceded the onset of gambling disorder. Six years passed between self-awareness of gambling problems and help-seeking. Two more years passed until exclusion. Frequent mental health problems suggest the need for individually tailored support beyond exclusion programmes (e.g. psychotherapy, pharmacotherapy, counselling services). Late help-seeking and exclusion entry claim for improved early detection and intervention concepts that consider underlying mental disorders.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Casino; co-morbidity; mental health; pathological gambling; self-exclusion

Heart rate and heart rate variability in panic, social anxiety, obsessive-compulsive, and generalized anxiety disorders at baseline and in response to relaxation and hyperventilation - Pittig, Andre; Arch, Joanna J.; Lam, Chi W. R.; Craske, Michelle G. (International Journal of Psychophysiology, 2013)
It remains unclear if diminished high frequency heart rate variability (HF-HRV) can be found across anxiety disorders. HF-HRV and heart rate (HR) were examined in panic (PD), generalized anxiety (GAD), social anxiety (SAD), and obsessive-compulsive disorder (OCD) relative to healthy controls at baseline and during anxiety stressors. All disorders evidenced diminished baseline HF-HRV relative to controls. Baseline HRV differences were maintained throughout relaxation. For hyperventilation, PD and GAD demonstrated greater HR than controls. Psychotropic medication did not account for HF-HRV differences except in OCD. Age and sex evidenced multiple main effects. Findings suggest that low baseline HF-HRV represents a common index for inhibitory deficits across PD, GAD, and SAD, which is consistent with the notion of autonomic inflexibility in anxiety disorders. Elevated HR responses to hyperventilation, however, are specific to PD and GAD. © 2012 Elsevier B.V.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety; Heart rate; Heart rate variability; Psychopathology

How depressive symptoms and fear of negative evaluation affect feedback evaluation in social decision-making - Weiß, Martin; Rodrigues, Johannes; Boschet, Juliane M.; Pittig, Andre; Mussel, Patrick; Hewig, Johannes (Journal of Affective Disorders, 2020)
Background The influence of emotional feedback on social decision-making situations is an omnipresent part of social interaction. Complementing existing research on the impact of approach- and avoidance-related personality traits, we examined the role of sub-clinical depression and fear of negative social evaluation in a modified ultimatum game. Methods Different proposer identities reacted with distinct affective facial expressions to the acceptance and rejection of monetary offers in the ultimatum game. Facial expressions of proposers were relevant for depression and anxiety: A smile in response to acceptance or angry and sad feedback in response to rejection. Results People with higher symptoms of depression rejected more offers when the offer magnitude increased. Both, individuals with symptoms of depression and fear of negative evaluation approached sad feedback by rejecting more offers. At the neural level, positive emotional feedback (i.e., a smiling face) was linked to a reward positivity, which did not occur in participants with higher symptoms of depression. Limitations Since our paradigm implies a decision-dependent feedback pattern, the negative feedback might have been expected and was therefore not perceived as particularly relevant. Conclusions The results indicate specific behavioral as well as neural reaction patterns, which can be used especially for an initial subclinical identification of depression.
Keywords: Emotional feedback; Fear of negative evaluation; Depression; Ultimatum game; Reward processing

Incentive-based extinction of safety behaviors: Positive outcomes competing with aversive outcomes trigger fear-opposite action to prevent protection from fear extinction - Pittig, Andre (Behaviour Research and Therapy, 2019)
Maladaptive safety behavior maintains fear and anxiety by prohibiting inhibitory learning about the non-occurrence of feared outcomes (known as protection from extinction). Not engaging in safety behavior, however, requires to act opposite to fear-motivated behavioral tendencies. The initiation of such fear-opposite action by positive outcomes, which were in conflict with safety behavior, was tested. Following fear acquisition to a warning signal (CS+), participants acquired safety behavior to prevent the aversive outcome (n = 48). Next, safety behavior also prevented gaining rewards. In a control group (n = 50), neutral outcomes were presented to control for novelty effects of the second outcome. Subsequently, no aversive outcome occurred anymore. Phases with safety behavior were intermitted by phases without safety behavior being available to examine cognitive and physiological indicators of fear and anxiety. Without competing positive outcomes, safety behavior was frequently executed, persisted in absence of the aversive outcome, and prohibited extinction learning. Positive outcomes clearly reduced safety behavior despite equal levels of acquired fear. This enabled fear extinction as soon as the aversive outcome was absent. Importantly, this extinction learning resulted in attenuated fear and anxiety responses when safety behavior became unavailable. Post-hoc findings indicated that the mere anticipation of positive outcomes slightly reduced safety behavior. Thus, competing positive outcomes triggered fear-opposite action that prevented persistent safety behavior and protection from extinction.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety; Avoidance; Fear conditioning; Fear extinction; Positive reinforcement; Safety behavior

Incentive-based, instructed, and social observational extinction of avoidance: Fear-opposite actions and their influence on fear extinction - Pittig, Andre; Wong, Alex H. K. (Behaviour Research and Therapy, 2021)
Avoidance is a transdiagnostic symptom of clinical anxiety and its reduction a major focus of cognitive-behavioral treatments. This study examined the instrumental extinction of goal-directed avoidance by means of incentives, verbal instruction, and social observation and their influence on fear extinction. Participants acquired conditioned fear and instrumental avoidance responses (N = 160). In four randomized groups, the reduction of avoidance by incentives for non-avoidance, instructions to refrain from avoidance, and social observation of non-avoidance was compared to no intervention before removing the aversive outcome. Conditioned fear when avoidance became unavailable subsequently was tested. Incentives, instruction, and observation all reduced avoidance better than no intervention, however, with different degrees and influence on conditioned fear. Incentives and instructions strongly reduced avoidance despite high levels of fear (i.e., fear-opposite actions). This initiated fear extinction, thereby reducing conditioned fear when avoidance became unavailable. Social observation directly reduced conditioned fear, presumably because it conveyed additional information about the absence of the aversive outcome. However, observation only moderately reduced avoidance and resulted in higher fear when avoidance became unavailable. The effects of social observation may depend on the nuances of the demonstrator's behavior. The clear effects of incentive and instructions provide support for clinical interventions to reduce avoidance during exposure therapy and can serve as experimental models for their controlled investigation.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety; Avoidance; Fear conditioning; Fear extinction; Fear-opposite action; Safety behavior

Increased anxiety of public situations during the COVID-19 pandemic: Evidence from a community and a patient sample - Pittig, Andre; Glück, Valentina M.; Boschet, Juliane M.; Wong, Alex H.K.; Engelke, Paula (Clinical Psychology in Europe, 2021)
Keywords: COVID-19; Anxiety; Public situations; Emotional distress

Inhibition of return in fear of spiders: Discrepant eye movement and reaction time data - Berdica, Elisa; Gerdes, Antje B. M.; Pittig, Andre; Alpers, Georg W. (Journal of Ophthalmology, 2014)
Inhibition of return (IOR) refers to a bias against returning the attention to a previously attended location. As a foraging facilitator it is thought to facilitate systematic visual search. With respect to neutral stimuli, this is generally thought to be adaptive, but when threatening stimuli appear in our environment, such a bias may be maladaptive. This experiment investigated the influence of phobia-related stimuli on the IOR effect using a discrimination task. A sample of 50 students (25 high, 25 low in spider fear) completed an IOR task including schematic representations of spiders or butterflies as targets. Eye movements were recorded and to assess discrimination among targets, participants indicated with button presses if targets were spiders or butterflies. Reaction time data did not reveal a significant IOR effect but a significant interaction of group and target; spider fearful participants were faster to respond to spider targets than to butterflies. Furthermore, eye-tracking data showed a robust IOR effect independent of stimulus category. These results offer a more comprehensive assessment of the motor and oculomotor factors involved in the IOR effect. © 2014 Elisa Berdica et al.
CRIS-Team Scopus Importer:2021-05-26

Instructed threat enhances threat perception in faces. - Kavcioglu, Fatih C.; Bublatzky, Florian; Pittig, Andre; Alpers, Georg W. (Emotion, 2021)
Anxiety can boost the detection of potential threats in many ways. There is evidence that one and the same facial expression can be perceived differently depending on whether it is seen in a neutral or in a threatening situation. The present study investigated how aversive anticipation influences the accuracy of facial emotion recognition and the perceived emotional intensity of faces that had their objective emotional intensity manipulated. Forty-three participants categorized and rated the intensity of morphed faces (20%, 40%, 60%, and 80%) of fearful, angry, and happy expressions. Differently colored picture frames indicated either threat of electric shock or safety. Threat of shock enhanced the categorization accuracy specifically for fearful faces. During threat, 80% fearful and happy faces, and all levels of angry faces (20%–80%) were rated as more intense. In addition, we found that more trait-anxious individuals more frequently erroneously categorized neutral faces as fearful. Thus, state anxiety enhanced accurate fear categorization and boosted the perceived intensity of emotional faces, whereas trait anxiety led to a biased threat perception in nonthreatening faces. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
CRIS-Team Scopus Importer:2021-05-26
Keywords: anxiety; emotional faces; face recognition; intensity ratings; threat of shock

Kognitive Verhaltenstherapie der Angststörungen - Heinig, Ingmar; Pittig, Andre; Hoyer, Juergen (Angst: Medizin. Psychologie. Gesellschaft, 2018)

Manualized cognitive therapy versus cognitive-behavioral treatment-as-usual for social anxiety disorder in routine practice: A cluster-randomized controlled trial - Hoyer, Juergen; Colic, Jasmin; Pittig, Andre; Crawcour, Stephen; Moeser, Manuela; Ginzburg, Denise; Lin, Jihong; Wiltink, Joerg; Leibing, Eric; Stangier, Ulrich (Behaviour Research and Therapy, 2017)
Objective This study examined the effectiveness of manualized cognitive therapy (mCT) following the Clark-Wells approach versus non-manualized cognitive-behavioral treatment-as-usual (CBTAU) for social anxiety disorder (SAD) in routine practice. Methods Forty-eight private practitioners were recruited within a multi-center trial and either received training in manualized CT for SAD or no such training. Practitioners treated 162 patients with SAD in routine practice (N = 107 completers, n = 57 for mCT, n = 50 for CBTAU). Social anxiety symptoms (Liebowitz Social Anxiety Scale; LSAS) and secondary measures were assessed before treatment, at treatment-hour 8, 15, and 25, at end of treatment, as well as 6 and 12 months after treatment. Results Patients in both groups showed significant reductions of SAD severity after treatment (d = 1.91 [mCT] and d = 1.80 [CBTAU], within-group effect sizes, intent-to-treat analyses, LSAS observer ratings), which remained stable at follow-up. There were no differences between groups in terms of symptom reduction and treatment duration. Conclusions The present trial confirms the high effectiveness of CBTAU and mCT for SAD when practitioners conduct the treatments in routine practice. Additional training in the CT manual did not result in significant between-group effects on therapy outcome. Explanations for this unexpected result are discussed.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Cognitive therapy; Cognitive-behavioral therapy; Naturalistic psychotherapy; Randomized controlled trial; Social anxiety disorder

Mapping Research Domain Criteria using a transdiagnostic mini-RDoC assessment in mental disorders: a confirmatory factor analysis - Foerstner, Bernd R.; Tschorn, Mira; Reinoso-Schiller, Nicolas; Maricic, Lea Mascarell; Roecher, Erik; Kalman, Janos L.; Stroth, Sanna; Mayer, Annalina V.; Schwarz, Kristina; Kaiser, Anna; Pfennig, Andrea; Manook, Andre; et al. (European archives of psychiatry and clinical neuroscience, 2022)
This study aimed to build on the relationship of well-established self-report and behavioral assessments to the latent constructs positive (PVS) and negative valence systems (NVS), cognitive systems (CS), and social processes (SP) of the Research Domain Criteria (RDoC) framework in a large transnosological population which cuts across DSM/ICD-10 disorder criteria categories. One thousand four hundred and thirty one participants (42.1% suffering from anxiety/fear-related, 18.2% from depressive, 7.9% from schizophrenia spectrum, 7.5% from bipolar, 3.4% from autism spectrum, 2.2% from other disorders, 18.4% healthy controls, and 0.2% with no diagnosis specified) recruited in studies within the German research network for mental disorders for the Phenotypic, Diagnostic and Clinical Domain Assessment Network Germany (PD-CAN) were examined with a Mini-RDoC-Assessment including behavioral and self-report measures. The respective data was analyzed with confirmatory factor analysis (CFA) to delineate the underlying latent RDoC-structure. A revised four-factor model reflecting the core domains positive and negative valence systems as well as cognitive systems and social processes showed a good fit across this sample and showed significantly better fit compared to a one factor solution. The connections between the domains PVS, NVS and SP could be substantiated, indicating a universal latent structure spanning across known nosological entities. This study is the first to give an impression on the latent structure and intercorrelations between four core Research Domain Criteria in a transnosological sample. We emphasize the possibility of using already existing and well validated self-report and behavioral measurements to capture aspects of the latent structure informed by the RDoC matrix.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Confirmatory factor analysis CFA; Diagnosis and classification; PD-CAN; RDoC; Research Domain Criteria; Transdiagnostic

Mechanisms of Change in Trauma-Focused Treatment for PTSD: The Role of Rumination - Schumm, Hannah; Krüger-Gottschalk, Antje; Dyer, Anne; Pittig, Andre; Cludius, Barbara; Takano, Keisuke; Alpers, Georg W.; Ehring, Thomas (Behaviour Research and Therapy, 2022)
Objective Cognitive behavioral therapy (CBT) has been well established in the treatment of posttraumatic stress disorder (PTSD). In recent years, researchers have begun to investigate its underlying mechanisms of change. Dysfunctional cognitive content, i.e. excessively negative appraisals of the trauma or its consequences, has been shown to predict changes in PTSD symptoms over the course of treatment. However, the role of change in cognitive processes, such as trauma-related rumination, needs to be addressed. The present study investigates whether changes in rumination intensity precede and predict changes in symptom severity. We also explored the extent to which symptom severity predicts rumination. Method As part of a naturalistic effectiveness study evaluating CBT for PTSD in routine clinical care, eighty-eight patients with PTSD completed weekly measures of rumination and symptom severity. Lagged associations between rumination and symptoms in the following week were examined using linear mixed models. Results Over the course of therapy, both ruminative thinking and PTSD symptoms decreased. Rumination was a significant predictor of PTSD symptoms in the following week, although this effect was at least partly explained by the time factor (e.g., natural recovery or inseparable treatment effects). Symptom severity predicted ruminative thinking in the following week even with time as an additional predictor. Conclusions The present study provides preliminary evidence that rumination in PTSD is reduced by CBT for PTSD but does not give conclusive evidence that rumination is a mechanism of change in trauma-focused treatment for PTSD.
Keywords: rumination; PTSD; Mechanisms of change; Trauma-focused treatment

Operante Verfahren - Junge-Hoffmeister, Juliane; Pittig, Andre; et al. (Klinische Psychologie & Psychotherapie. 3. Aufl., 2021)

Optimierung expositionsbasierter Therapie: Ein Ansatz des inhibitorischen Lernens - Pittig, Andre; Stevens, Stephan; Vervliet, Bram; Treanor, Michael; Conway, Christopher C.; Zbozinek, Tomislav; Craske, Michelle G. (Psychotherapeut, 2015)
Keywords: Exposure therapy; Extinction; Case studies; Clinical application; Anxiety disorders

Optimierung expositionsbasierter Therapie: Ein Ansatz des inhibitorischen Lernens - Pittig, Andre; Stevens, Stephan; Vervliet, Bram; Treanor, Michael; Conway, Christopher C.; Zbozinek, Tomislav; Craske, Michelle G. (Psychotherapeut, 2015)
Exposure is an effective approach for treating anxiety disorders, although a substantial number of individuals fail to benefit or experience a return of fear. Research results suggest that anxious individuals show deficits in the mechanisms underlying exposure therapy, such as inhibitory learning. Targeting these processes may help improve the efficacy of exposure; however, there has been little discussion of how to implement this model in clinical practice. The primary aim of this paper is to provide examples to clinicians for how to apply this model to optimize exposure therapy, in ways that distinguish it from a fear habituation approach and a belief disconfirmation approach. Optimization strategies include (1) expectancy violation, (2) deepened extinction, (3) occasional reinforced extinction, (4) removal of safety signals, (5) variability, (6) retrieval cues, (7) multiple contexts and (8) affect labeling. Case studies illustrate methods of applying these techniques with a variety of anxiety disorders.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Case studies; Clinical application; Exposure therapy; Extinction

Optimizing exposure-based CBT for anxiety disorders via enhanced extinction: Design and methods of a multicentre randomized clinical trial - Heinig, Ingmar; Pittig, Andre; Richter, Jan; Hummel, Katrin; Alt, Isabel; Dickhoever, Kristina; Gamer, Jennifer; Hollandt, Maike; Koelkebeck, Katja; Maenz, Anne; Tennie, Sophia; Totzeck, Christina; et al. (International Journal of Methods in Psychiatric Research, 2017)
Exposure-based psychological interventions currently represent the empirically best established first line form of cognitive-behavioural therapy for all types of anxiety disorders. Although shown to be highly effective in both randomized clinical and other studies, there are important deficits: (1) the core mechanisms of action are still under debate, (2) it is not known whether such treatments work equally well in all forms of anxiety disorders, including comorbid diagnoses like depression, (3) it is not known whether an intensified treatment with more frequent sessions in a shorter period of time provides better outcome than distributed sessions over longer time intervals. This paper reports the methods and design of a large-scale multicentre randomized clinical trial (RCT) involving up to 700 patients designed to answer these questions. Based on substantial advances in basic research we regard extinction as the putative core candidate model to explain the mechanism of action of exposure-based treatments. The RCT is flanked by four add-on projects that apply experimental neurophysiological and psychophysiological, (epi)genetic and ecological momentary assessment methods to examine extinction and its potential moderators. Beyond the focus on extinction we also involve stakeholders and routine psychotherapists in preparation for more effective dissemination into clinical practice.
CRIS-Team Scopus Importer:2021-05-26
Keywords: anxiety disorders; exposure therapy; extinction; randomized clinical trial

Physiological and behavioral indices of emotion dysregulation as predictors of outcome from cognitive behavioral therapy and acceptance and commitment therapy for anxiety - Davies, Carolyn D.; Niles, Andrea N.; Pittig, Andre; Arch, Joanna J.; Craske, Michelle G. (Journal of Behavior Therapy and Experimental Psychiatry, 2015)
Background and objectives Identifying for whom and under what conditions a treatment is most effective is an essential step toward personalized medicine. The current study examined pre-treatment physiological and behavioral variables as predictors and moderators of outcome in a randomized clinical trial comparing cognitive behavioral therapy (CBT) and acceptance and commitment therapy (ACT) for anxiety disorders.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Acceptance and commitment therapy; Behavioral avoidance; Cognitive behavioral therapy; Heart rate variability; Treatment outcome

Public speaking avoidance as a treatment moderator for social anxiety disorder - Mesri, Bita; Niles, Andrea N.; Pittig, Andre; Lebeau, Richard T.; Haik, Ethan; Craske, Michelle G. (Journal of Behavior Therapy and Experimental Psychiatry, 2017)
Background and objectives Cognitive behavioral therapy (CBT) and acceptance and commitment therapy (ACT) have both garnered empirical support for the effective treatment of social anxiety disorder. However, not every patient benefits equally from either treatment. Identifying moderators of treatment outcome can help to better understand which treatment is best suited for a particular patient. Methods Forty-nine individuals who met criteria for social anxiety disorder were assessed as part of a randomized controlled trial comparing 12 weeks of CBT and ACT. Pre-treatment avoidance of social situations (measured via a public speaking task and clinician rating) was investigated as a moderator of post-treatment, 6-month follow-up, and 12-month follow-up social anxiety symptoms, stress reactivity, and quality of life. Results Public speaking avoidance was found to be a robust moderator of outcome measures, with more avoidant individuals generally benefitting more from CBT than ACT by 12-month follow-up. In contrast, clinician-rated social avoidance was not found to be a significant moderator of any outcome measure. Limitations Results were found only at 12-month follow-up. More comprehensive measures of avoidance would be useful for the field moving forward. Conclusions Findings inform personalized medicine, suggesting that social avoidance measured behaviorally via a public speaking task may be a more robust factor in treatment prescription compared to clinician-rated social avoidance.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Acceptance and commitment therapy; Cognitive behavioral therapy; Moderator; Social anxiety; Treatment outcome

Reducing the return of avoidance and fear by directly targeting avoidance: Comparing incentive-based and instructed extinction of avoidance to passive fear extinction - Pittig, Andre; Wong, Alex H. K. (Journal of Experimental Psychopathology, 2022)
Enhancing the reduction of avoidance may optimize treatment for anxiety disorders. Past research focused on boosting fear extinction to reduce avoidance, however, with limited success. Directly extinguishing avoidance may be more promising. This preregistered study tested the impact of incentives and instruction for non-avoidance compared to passive fear extinction on long-term avoidance and fear reduction. On Day 1, participants acquired conditioned fear and avoidance to a conditioned stimulus (CS) paired with an aversive outcome. Next, incentives or instructions encouraged non-avoidance to the CS, which was no longer reinforced by a US regardless of avoidance (Incentives and Instruction group). In a third group, avoidance was unavailable and the CS was passively presented in absence of the US (Passive Fear Extinction group). On Day 2, avoidance retention and reinstatement and return of fear were tested. In the short term, incentives and instruction strongly reduced avoidance with similar fear reduction compared to passive fear extinction. Importantly, incentives and instruction were linked to lower long-term avoidance retention. Avoidance reinstatement was evident in all groups, but avoidance remained higher after passive fear extinction. Finally, incentives yielded a lower return of threat expectancies. Thus, targeting avoidance instead of fear better reduced long-term avoidance and, for incentives, the return of fear. Especially, incentives could be a promising add-on to exposure.
CRIS-Team WoS Importer:2023-03-03

Reduction of costly safety behaviors after extinction with a generalization stimulus is determined by individual differences in generalization rules - Wong, Alex H.K.; Lee, Jessica C.; Engelke, Paula; Pittig, Andre (Behaviour Research and Therapy, 2023)
Exposure-based treatment involves repeated presentation of feared stimuli or situations in the absence of perceived threat (i.e., extinction learning). However, the stimulus or situation of fear acquisition (CS+) is highly unlikely to be replicated and presented during treatment. Thereby, stimuli that resemble the CS+ (generalization stimuli; GSs) are typically presented. Preliminary evidence suggests that depending on how one generalizes fear (i.e., different generalization rules), presenting the same GS in extinction leads to differential effectiveness of extinction learning. The current study aimed to extend this finding to safety behaviors. After differential fear and avoidance conditioning, participants exhibited discrete generalization gradients that were consistent with their reported generalization rules (Similarity vs Linear). The Linear group showed stronger safety behaviors to a selected GS compared to the Similarity group, presumably due to higher threat expectancy. After extinction learning to this GS, the Linear group exhibited stronger reduction in safety behaviors generalization compared to the Similarity group. The results show that identifying distinct generalization rules allows one to predict expectancy violation to the extinction stimulus, in addition to corroborating the idea that strongly violating threat expectancy leads to better extinction learning and its generalization. With regard to clinical implications, identifying one's generalization rule (e.g., threat beliefs) help designing exposure sessions that evoke strong expectancy violation, enhancing the reduction in the generalization of maladaptive safety behaviors.
CRIS-Team Scopus Importer:2022-12-09

Reduction of depersonalization during social stress through cognitive therapy for social anxiety disorder: A randomized controlled trial - Schweden, Tabea L. K.; Pittig, Andre; Brauer, David; Klumbies, Elisabeth; Kirschbaum, Clemens; Hoyer, Juergen (Journal of Anxiety Disorders, 2016)
Symptoms of depersonalization during feared social situations are commonly experienced by individuals with social anxiety disorder (SAD). Despite its clinical relevance, it is not addressed in standard treatment manuals and it remains unclear if depersonalization is reduced by well-established treatments. This study investigated whether cognitive therapy (CT) for SAD effectively reduces depersonalization and whether pre-treatment severity of depersonalization predicts or mediates treatment outcome. In a randomized controlled trial, patients underwent the standardized Trier Social Stress Test before and after CT (n = 20) or a waitlist period (n = 20) and were compared to healthy controls (n = 21). Self-reported depersonalization was measured immediately after each stress test. Depersonalization significantly decreased following CT, especially in treatment responders (ηp2 = 0.32). Pre-treatment depersonalization did neither predict nor mediate post-treatment severity of social anxiety. Further prospective studies are needed for a better scientific understanding of this effect. It should be scrutinized whether SAD-patients suffering from depersonalization would benefit from a more specific therapy.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Cognitive therapy; Depersonalization; Derealization; Dissociation; Social anxiety disorder; Social phobia

Same fear responses, less avoidance: Rewards competing with aversive outcomes do not buffer fear acquisition, but attenuate avoidance to accelerate subsequent fear extinction - Pittig, Andre; Dehler, Jule (Behaviour Research and Therapy, 2019)
Rewards for approaching a feared stimulus may compete with fear reduction inherent to avoidance and thereby alter fear and avoidance learning. However, the impact of such competing rewards on fear and avoidance acquisition has rarely been investigated. During acquisition, participants chose between one option (CS+ option) associated with a neutral stimulus followed by an aversive unconditioned stimulus (US) and another option (CS− option) associated with another neutral stimulus followed by no US (N = 223 randomized into three groups). In a subsequent test, no more USs occurred. In one group, competing rewards were established by linking the CS+ option to high rewards and the CS− option to low rewards during acquisition and test (Reward Group). In a second group, rewards were present during acquisition, but discontinued during test (Initial-Reward Group). In a third group, rewards were completely absent (No-Reward Group). Without competing rewards, significant avoidance was acquired and persisted in the absence of the US. Competing rewards attenuated avoidance acquisition already after the first experience of the aversive US. Avoidance remained attenuated even when rewards were discontinued during test. Rewards did, however, not change the level of fear responses to the CS+ (US expectancy, skin conductance). Finally, rewards did not change the level of fear reduction during test, which was, however, experienced earlier. Summarized, rewards for approaching aversive events do not buffer fear acquisition, but can prevent avoidance. This damping of avoidance may initiate fear extinction.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Approach-avoidance; Avoidance conditioning; Behavioral avoidance; Fear; Fear conditioning

Smart-Glass Guided Exposure for Anxiety Disorders: A Proof-of-Concept Study - Pittig, Andre; Hoyer, Jürgen; Noack, René (Cognitive and Behavioral Practice, 2021)
Exposure is a highly effective treatment for pathological fear and anxiety, but rarely used in routine care. Issues of practicability and lack of therapists in rural areas are main barriers for the dissemination of exposure. Smartglass devices may enable therapists to guide exposure from their own office via real-time feedback and may thereby increase practicability. The present study explored the technological usability and clinical feasibility of Smartglass-guided exposure in a behavioral approach test in spider-fearful individuals (N = 40). Fearful individuals were asked to start the Smartglass themselves and established a connection to a therapist, who guided the exposure test from afar. Clinical severity of spider fear was assessed via questionnaire. Technological usability was assessed with established measures of usability, user experience, and user acceptance. Exploratory, individual characteristics of exposure were collected (e.g., within-session fear reduction, duration, safety behavior). Overall, fearful individuals (94.9%) and therapists (100%) were able to establish a connection. Usability of Smartglass-guided exposure was evaluated as positive. Within-session fear reduction was large (d = 1.91). Adverse events were minimal. There were, however, some associations between exposure characteristics and usability evaluation (e.g., lower user-friendliness and exposure duration). Two case examples further highlight chances and risks of Smartglass-guided exposure. These findings provide first evidence that Smartglass-guided exposure could be useful in exposure therapy. Smartglass-guided exposure may ultimately help to increase practicability of exposure and increase dissemination, also in rural areas. These findings are promising for future research on the long-term outcome of evidence-based exposure in treatment seeking patients.
CRIS-Team Scopus Importer:2021-05-26
Keywords: anxiety disorders; dissemination; exposure; fear of spiders; smart glass

Social and monetary incentives counteract fear-driven avoidance: Evidence from approach-avoidance decisions - Pittig, Andre; Hengen, Kristina; Bublatzky, Florian; Alpers, Georg W. (Journal of Behavior Therapy and Experimental Psychiatry, 2018)
Background and Objectives: The reduction of avoidance behavior is a central target in the treatment of anxiety disorders, but it has rarely been studied how approach of fear-relevant stimuli may be initiated. In two studies, the impact of hypothetical monetary and symbolic social incentives on approach-avoidance behavior was examined. Methods: In Study 1, individuals high or low on fear of spiders (N = 84) could choose to approach a fear-relevant versus a neutral stimulus, which were equally rewarded. In a subsequent micro-intervention, approaching the fear-relevant stimulus was differentially rewarded either by monetary or social incentives. In Study 2 (N = 76), initial incentives for approach were discontinued to investigate the stability of approach. Results: Hypothetical monetary and symbolic social incentives reduced or eliminated initial avoidance, even in highly fearful individuals. Approach resulted in a decrease of self-reported aversiveness towards the fear-relevant stimulus. However, even after successful approach, fearful individuals showed significant avoidance behavior when incentives for approach were discontinued. Limitations: Future research should investigate the long-term effects of prolonged approach incentives on multiple levels of fear (e.g., self-report, behavioral, physiological). It should also be tested if such an intervention actually improves compliance with exposure based interventions. Conclusions: The present findings highlight that incentives are useful to initiate initial approach towards a feared stimulus. Although incentive-based approach may neither fully eliminate avoidance nor negative feelings towards the feared stimulus, such operant interventions may set the stage for more extensive extinction training.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Avoidance; Decision making; Exposure therapy; Fear; Operant training; Spider phobia

Sometimes I feel the fear of uncertainty: How intolerance of uncertainty and trait anxiety impact fear acquisition, extinction and the return of fear - Wroblewski, Adrian; Hollandt, Maike; Yang, Yunbo; Ridderbusch, Isabelle C.; Pietzner, Anne; Szeska, Christoph; Lotze, Martin; Wittchen, Hans Ulrich; Heinig, Ingmar; Pittig, Andre; Arolt, Volker; Koelkebeck, Katja; et al. (International Journal of Psychophysiology, 2022)
It is hypothesized that the ability to discriminate between threat and safety is impaired in individuals with high dispositional negativity, resulting in maladaptive behavior. A large body of research investigated differential learning during fear conditioning and extinction protocols depending on individual differences in intolerance of uncertainty (IU) and trait anxiety (TA), two closely-related dimensions of dispositional negativity, with heterogenous results. These might be due to varying degrees of induced threat/safety uncertainty. Here, we compared two groups with high vs. low IU/TA during periods of low (instructed fear acquisition) and high levels of uncertainty (delayed non-instructed extinction training and reinstatement). Dependent variables comprised subjective (US expectancy, valence, arousal), psychophysiological (skin conductance response, SCR, and startle blink), and neural (fMRI BOLD) measures of threat responding. During fear acquisition, we found strong threat/safety discrimination for both groups. During early extinction (high uncertainty), the low IU/TA group showed an increased physiological response to the safety signal, resulting in a lack of CS discrimination. In contrast, the high IU/TA group showed strong initial threat/safety discrimination in physiology, lacking discriminative learning on startle, and reduced neural activation in regions linked to threat/safety processing throughout extinction training indicating sustained but non-adaptive and rigid responding. Similar neural patterns were found after the reinstatement test. Taken together, we provide evidence that high dispositional negativity, as indicated here by IU and TA, is associated with greater responding to threat cues during the beginning of delayed extinction, and, thus, demonstrates altered learning patterns under changing environments.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Dispositional negativity; Fear conditioning; fMRI; Intolerance of uncertainty; Psychophysiology; Trait anxiety

The cost of fear: Avoidant decision making in a spider gambling task - Pittig, Andre; Brand, Matthias; Pawlikowski, Mirko; Alpers, Georg W. (Journal of Anxiety Disorders, 2014)
Individuals with anxiety disorders typically avoid fear-relevant stimuli even if they miss potential rewards. However, few studies have accounted for such costs of fear-related avoidance in doing so. In this study, 51 spider fearful and 49 non-fearful participants completed the Spider Gambling Task, our modification of the Iowa Gambling Task, to investigate whether fear-relevant stimuli trigger avoidant decisions in the presence of potential rewards. In one version, advantageous choices were associated with pictures of spiders, whereas the same pictures were associated with disadvantageous choices in another version. Fearful participants generally avoided choices associated with pictures of spiders, which resulted in lower overall gains in the version with advantageous spider decks. Although this relative avoidance was sustained, fearful participants progressively approach more advantageous spider choices. These findings demonstrate that phobic fear results in irrational avoidant decisions which can result in considerable cost. Potential long-term rewards for approach may, however, diminish absolute avoidance behavior. © 2014.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Behavioral avoidance; Decision making; Experimental psychopathology; Fear; Spider phobia

The key role of extinction learning in anxiety disorders: Behavioral strategies to enhance exposure-based treatments - Pittig, Andre; Van Den Berg, Linda; Vervliet, Bram (Current Opinion in Psychiatry, 2016)
Purpose of review Extinction learning is a major mechanism for fear reduction by means of exposure. Current research targets innovative strategies to enhance fear extinction and thereby optimize exposure-based treatments for anxiety disorders. This selective review updates novel behavioral strategies that may provide cutting-edge clinical implications. Recent findings Recent studies provide further support for two types of enhancement strategies. Procedural enhancement strategies implemented during extinction training translate to how exposure exercises may be conducted to optimize fear extinction. These strategies mostly focus on a maximized violation of dysfunctional threat expectancies and on reducing context and stimulus specificity of extinction learning. Flanking enhancement strategies target periods before and after extinction training and inform optimal preparation and postprocessing of exposure exercises. These flanking strategies focus on the enhancement of learning in general, memory (re-)consolidation, and memory retrieval. Summary Behavioral strategies to enhance fear extinction may provide powerful clinical applications to further maximize the efficacy of exposure-based interventions. However, future replications, mechanistic examinations, and translational studies are warranted to verify long-term effects and naturalistic utility. Future directions also comprise the interplay of optimized fear extinction with (avoidance) behavior and motivational antecedents of exposure.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Enhancement strategies; Exposure therapy; Fear extinction; Inhibitory learning

The riskiest psychological intervention? Positive and negative side effects of exposure for anxiety disorders - Heinig, Ingmar; Knappe, Susanne; Wittchen, Hans-Ulrich; Hoyer, Juergen; Arolt, Volker; Diaeresis, Juergen; Domschke, Katharina; Kircher, Tilo; Margraf, Juergen; Straube, Benjamin; Stroehle, Andreas; Hamm, Alfons; et al. (JOURNAL OF NEURAL TRANSMISSION, 2021)
CRIS-Team WoS Importer:2021-11-19

The role of associative fear and avoidance learning in anxiety disorders: Gaps and directions for future research - Pittig, Andre; Treanor, Michael; Lebeau, Richard T.; Craske, Michelle G. (Neuroscience and Biobehavioral Reviews, 2018)
Anxiety disorders are the most common mental disorders and are often chronic and disabling. Although exposure-based treatments are effective, a substantial number of individuals fail to fully remit or experience a return of symptoms after treatment. Understanding the critical processes underlying the development and treatment of anxiety disorders will help identify individuals at risk and optimize treatments. Aversive associative learning offers explanatory pathways through which fear and anxiety emerge, spread, persist, and resurge. This narrative review examines the advances made in our understanding of associative fear and avoidance learning in anxiety disorders. Overall, the extant literature supports a key role of aversive associative learning in the development and treatment of anxiety disorders. However, research targeting specific mechanisms such as extinction generalization and avoidance, the fragility of extinction, and moderating influences of individual differences pertinent to anxiety disorders (e.g., age, sex, depression) is needed. We discuss the need for more ecological valid and complex paradigms to model ambiguity and conflict as well as for clinical translation studies to optimize treatment.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Associative learning; Aversive learning; Avoidance; Exposure; Extinction; Fear conditioning

The Struggle of Behavioral Therapists With Exposure: Self-Reported Practicability, Negative Beliefs, and Therapist Distress About Exposure-Based Interventions - Pittig, Andre; Kotter, Roxana; Hoyer, Juergen (Behavior Therapy, 2019)
Exposure-based interventions are a core ingredient of evidence-based cognitive-behavioral treatment (CBT) for anxiety disorders, posttraumatic stress disorder (PTSD), and obsessive-compulsive disorder (OCD). However, previous research has documented that exposure is rarely utilized in routine care, highlighting an ongoing lack of dissemination. The present study examined barriers for the dissemination of exposure from the perspective of behavioral psychotherapists working in outpatient routine care (N = 684). A postal survey assessed three categories of barriers: (a) practicability of exposure-based intervention in an outpatient private practice setting, (b) negative beliefs about exposure, and (c) therapist distress related to the use of exposure. In addition, self-reported competence to conduct exposure for different anxiety disorders, PTSD, and OCD was assessed. High rates of agreement were found for single barriers within each of the three categories (e.g., unpredictable time management, risk of uncompensated absence of the patient, risk of decompensation of the patient, superficial effectiveness, or exposure being very strenuous for the therapist). Separately, average agreement to each category negatively correlated with self-reported utilization of exposure to a moderate degree (-.35 ≤ r ≤ -.27). In a multiple regression model, only average agreement to barriers of practicability and negative beliefs were significantly associated with utilization rates. Findings illustrate that a multilevel approach targeting individual, practical, and systemic barriers is necessary to optimize the dissemination of exposure-based interventions. Dissemination efforts may therefore benefit from incorporating strategies such as modifying negative beliefs, adaptive stress management for therapists, or increasing practicability of exposure-based interventions.
CRIS-Team Scopus Importer:2021-05-26
Keywords: anxiety disorders; dissemination; exposure therapy; obsessive-compulsive disorder; posttraumatic stress disorder

Threat belief determines the degree of costly safety behavior: Assessing rule-based generalization of safety behavior with a dimensional measure of avoidance - Wong, Alex H.K.; Pittig, Andre (Behaviour Research and Therapy, 2022)
Excessive generalization of safety behavior to innocuous stimuli that resemble a feared stimulus is oftentimes pathological especially with inflicted impairments. Safety behavior is conventionally assessed dichotomously, requiring multiple presentations of each test stimulus for assessing the proportion of safety behavior executed. Thus, the generalization gradient confounds with ongoing extinction learning during non-reinforced test trials. The present study employed a recently developed dimensional measure of avoidance to examine the extent of safety behavior generalization. We found that a dimensional measure of avoidance was able to assess the generalization gradients of safety behavior even when each test stimulus was presented once, thus minimizing the effect of ongoing extinction learning. Of equal importance is whether higher-order cognitive processes shape generalization of safety behavior. We found a range of distinct generalization gradients in safety behavior, which were highly consistent with participants’ verbally reported relational rules. This rule-based generalization parallels to how clinically anxious individuals develop different threat beliefs after trauma exposure, and models how these distinct threat beliefs determine the extent of safety behavior engagement.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Extinction; Fear conditioning; Fear generalization; Rule-based generalization; Safety behavior; Threat beliefs

Threat belief determines the degree of costly safety behavior: assessing rule-based generalization of safety behavior with a dimensional measure of avoidance - Wong, Alex; Pittig, Andre (JOURNAL OF NEURAL TRANSMISSION, 2021)
CRIS-Team WoS Importer:2021-11-19

Yoga effectively reduces fatigue and symptoms of depression in patients with different types of cancer - Zetzl, Teresa; Renner, Agnes; Pittig, Andre; Jentschke, Elisabeth; Roch, Carmen; Van Oorschot, Birgitt (Supportive Care in Cancer, 2021)
Purpose: Examine the effects of an 8-week yoga therapy on fatigue in patients with different types of cancer. Methods: A total of 173 cancer patients suffering from mild to severe fatigue were randomly allocated to yoga intervention (n = 84) (IG) versus waitlist control group (CG) (n = 88). Yoga therapy consisted of eight weekly sessions with 60 min each. The primary outcome was self-reported fatigue symptoms. Secondary outcomes were symptoms of depression and quality of life (QoL). Data were assessed using questionnaires before (T0) and after yoga therapy for IG versus waiting period for CG (T1). Results: A stronger reduction of general fatigue (P =.033), physical fatigue (P =.048), and depression (P <.001) as well as a stronger increase in QoL (P =.002) was found for patients who attended 7 or 8 sessions compared with controls. Within the yoga group, both higher attendance rate and lower T0-fatigue were significant predictors of lower T1-fatigue (P ≤.001). Exploratory results revealed that women with breast cancer report a higher reduction of fatigue than women with other types of cancer (P =.016) after yoga therapy. Conclusion: The findings support the assumption that yoga therapy is useful to reduce cancer-related fatigue, especially for the physical aspects of fatigue. Women with breast cancer seem to benefit most, and higher attendance rate results in greater reduction of fatigue. Trial registration: German Clinical Trials Register DRKS00016034
CRIS-Team Scopus Importer:2021-05-26
Keywords: Complementary alternative medicine; Depression; Fatigue; Mind-body intervention; Quality of life; Yoga

Yoga therapy to reduce fatigue in cancer: effects of reminder e-mails and long-term efficacy - Zetzl, Teresa; Pittig, Andre; Renner, Agnes; Van Oorschot, Birgitt; Jentschke, Elisabeth (Supportive Care in Cancer, 2021)
Objective To examine the efficacy of reminder e-mails to continue yoga therapy on practice frequency and fatigue in cancer patients and long-term effects of yoga on fatigue, depression, and quality of life. Methodology One hundred two cancer patients who completed an 8-week yoga therapy were randomly allocated to two groups: reminder (N = 51) vs. no-reminder group (N = 51). After completing yoga therapy, the reminder group received weekly e-mails for 24 weeks, which reminded them of practicing yoga, whereas the no-reminder group did not. Primary outcomes were fatigue and practice frequency, and long-term outcomes were fatigue, depression, and quality of life. Data were assessed using questionnaires after yoga therapy (T1) and 6 months after completing yoga therapy (T2). Result A significantly stronger reduction of general (p = 0.038, d = 0.42) and emotional fatigue (p = 0.004, d = 0.59) and a higher increase of practice frequency (p = 0.015, d = 0.52) between T1 and T2 were found for the reminder group compared to the no-reminder group. In the mediation model, practice frequency as a mediator partially explained the changes in emotional fatigue (indirect effect B = - 0.10). Long-term effects of yoga therapy regarding fatigue, depression, and quality of life were found (F > 7.46, p < 0.001, d > 0.54). Conclusion Weekly reminder e-mails after yoga therapy can positively affect general and emotional fatigue and help cancer patients with fatigue establish a regular yoga practice at home. However, higher practice frequency did not lead to higher physical or cognitive fatigue improvement, suggesting other factors that mediate efficacy on physical or cognitive fatigue, such as mindfulness or side effects of therapy.
Keywords: Mind-body intervention; Complementary alternative medicine; Long-term effects; Yoga; Fatigue; Reminder e-mails